Lost virtue professional character development in medical education - Kenny, Nuala P.; Shelton, Wayne N. (Amsterdam ; Oxford : Elsevier, 2006)
Discusses character formation, ethics, professional character, and other concepts and addresses the interpersonal aspects of physicians as well as the importance of character.
Introduction: Lost virtue: professional character development and medical education / Nuala Kenny, Wayne Shelton -- Character formation and the making of good physicians / Edmund Pellegrino -- The ethical concept of medicine as a profession: its origins in modern medical ethics and implications for physicians / Laurence B. McCullough -- Character formation in professional education: a word of caution / Robert M. Veatch -- Evidence-based character development / Muriel J. Bebeau -- Disillusioned doctors / Carl Elliott -- Molding professional character / Rosamond Rhodes, Lawrence G. Smith -- Mindful practice and the tacit ethics of the moment / Ronald M. Epstein -- Learning and teaching in professional character development / Karen V. Mann -- The medical-social education compact and the medical learner / David J. Doukas -- Searching for doctor good: virtues for the twenty-first century / Nuala Kenny.
Includes bibliographical references.
Description based on print version record.
Keywords: Medical ethics; Medical ethics -- Study and teaching; Moral education (Higher); Medical ethics & professional conduct; Medical -- Education & Training; Medical -- Ethics